ANALISIS PERUBAHAN STRUKTUR LEMBAGA NEGARA DAN SISTIM PENYELENGGARAAN KEKUASAAN NEGARA REPUBLIK INDONESIA BERDASARKAN UNDANG-UNDANG DASAR 1945 SEBELUM DAN SESUDAH AMANDEMEN - H. ISMAIL MZ (GANEC SWARA, 2019)
The amendment to the 1945 Constitution after the 1998 reform is based on the experience of the practice of state administration by the old and new order governments which are often referred to as authoritarian government systems, both overt and covert. The 1945 Constitution indeed gives enormous power to the President, both Sukarno and Suharto. Weaknesses contained in the 1945 Constitution that triggers the birth of the demands of the reformists to make amendments to the 1945 Constitution, especially concerning the power and term of office of the President. It is important to realize that after the 1945 Constitution is amended, it has very basic implications for the structure of the Republic of Indonesia. Before the amendment to the 1945 Constitution the existing state institutions are the People's Consultative Assembly, the President, the People's Representative Council, the Supreme Consultative Council, the Supreme Audit Board and the Supreme Court, whose titles are divided into two, namely the highest state institutions which are embedded in the People's Consultative Assembly, and the other is a high-level state institution.   After changes or amendments to the 1945 Constitution from 1999 to 2002 have implications for changes in the structure of existing state institutions and the number becomes more than before the change. The state institutions after the change are explicitly mentioned in the nomenclature such as: the People's Consultative Assembly, the House of Representatives, the Regional Representative Council, the Regional People's Representative Council, the President and Vice President, the Minister (Specially the Minister of the Interior, the Minister of Foreign Affairs and the Minister of Defense ) Governor, Regent, Mayor, Indonesian National Army, Republic of Indonesia National Police, Supreme Court, Constitutional Court, Judicial Commission and Supreme Audit Board. While there are other state institutions whose nomenclature is not mentioned explicitly namely; Advisory Council, Election Commission and Central Bank. As a consequence of the amendment to the 1945 Constitution, the constitutional system adopted has also changed. If before the change to the constitutional system adopted is the cameral union representative system, but after the change into the bicameral system, some even called it tri kameral